2023
DOI: 10.2174/1573394719666230427094247
|View full text |Cite
|
Sign up to set email alerts
|

Echinococcus granulosus as a Promising Therapeutic Agent against Triplenegative Breast Cancer

Abstract: Breast cancer is a major cause of cancer deaths in women, with approximately 1.2 million new cases per year. Current treatment options for breast cancer include surgery, radiation, hormone therapy, and chemotherapy. However, the non-selective cytotoxicity of chemotherapeutic agents often leads to severe side effects, while drug resistance can worsen patient outcomes. Therefore, the development of more effective and less toxic anticancer drugs is a critical need. This study aimed to review the literature on Ech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…17,18 The adult form of Echinococcus granulosus (Sensu Lato) is located in the definitive host's small intestine. 19,20 Gravid proglottids release their eggs into the feces, and a suitable intermediate host then ingests them. 21,22 The eggs hatch in the small intestine and release six hooked oncospheres, which can pass through the intestinal wall and migrate through the circulatory system to various organs, especially the liver and lungs.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 The adult form of Echinococcus granulosus (Sensu Lato) is located in the definitive host's small intestine. 19,20 Gravid proglottids release their eggs into the feces, and a suitable intermediate host then ingests them. 21,22 The eggs hatch in the small intestine and release six hooked oncospheres, which can pass through the intestinal wall and migrate through the circulatory system to various organs, especially the liver and lungs.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Employing pathogenic microorganisms in cancer immunotherapy is not new. Serratia spp, 13 Streptococcus spp, 14 Listeria monocytogenes, 15 Escherichia coli, 16 Lactobacillus casei, 17 Oncolytic virus, 18 Talimogene laherparepve, 19 Newcastle disease virus, 20 yellow fever vaccine 17D, 21 Trypanosoma cruzi, 22 Echinococcus granulosus, 23,24 and Trichinella spiralis, 25 have been shown to eradicate tumor cells. 26 Toxoplasma gondii (T. gondii) can regulate innate immune cells by invading myeloid cells, typically producing powerful Th1 immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, immunotherapy has played an important role in cancer treatment, standing as the fourth treatment pathway following surgery, chemotherapy, and radiotherapy as the fourth major treatment pathway 3 . In-vitro experiments have shown that certain parasites, including the protozoans Toxoplasma gondii, Trypanosoma cruzi, and the helminths Trichinella spiralis and Echinococcus granulosus represent anti-cancer activities [4][5][6][7] . Nanovaccines are a promising strategy due to their increased lowest immunotoxicity, antigen stability, flexibility of the physical characteristics of nanomaterials, and sustained release.…”
Section: Introductionmentioning
confidence: 99%